2019
DOI: 10.1097/sla.0000000000003462
|View full text |Cite
|
Sign up to set email alerts
|

Description and Impact of a Comprehensive Multispecialty Multidisciplinary Intervention to Decrease Opioid Prescribing in Surgery

Abstract: Introduction: Diversion of excess prescription opioids contributes to the opioid epidemic. We sought to describe and study the impact of a comprehensive departmental initiative to decrease opioid prescribing in surgery. Methods: A multispecialty multidisciplinary initiative was designed to change the culture of postoperative opioid prescribing, including: consensus-built opioid guidelines for 42 procedures from 11 specialties, provider-focused posters d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…Provider education and implementing procedure-specific prescribing guidelines for discharge have consistently been shown to reduce new persistent opioid use [18,[31][32][33][34]. In a study by Kaafarni et al (2019), persistent postoperative opioid use was decreased after implementation of a multidisciplinary intervention including opioid guidelines for procedures from 11 different specialties, provider-focused posters displayed in all surgical units, patient opioid/pain brochures setting expectations, and educational seminars to residents, advanced practice providers, and nurses [35]. Similarly, a 2020 study by Patel et al found that implementing an opioid reduction intervention consisting of an informational sheet for patients at discharge, education by nurses at discharge, and an evidence-based prescribing guideline resulted in decreased opioid usage in the first 30 days after surgery [36].…”
Section: Postoperative Interventionsmentioning
confidence: 99%
“…Provider education and implementing procedure-specific prescribing guidelines for discharge have consistently been shown to reduce new persistent opioid use [18,[31][32][33][34]. In a study by Kaafarni et al (2019), persistent postoperative opioid use was decreased after implementation of a multidisciplinary intervention including opioid guidelines for procedures from 11 different specialties, provider-focused posters displayed in all surgical units, patient opioid/pain brochures setting expectations, and educational seminars to residents, advanced practice providers, and nurses [35]. Similarly, a 2020 study by Patel et al found that implementing an opioid reduction intervention consisting of an informational sheet for patients at discharge, education by nurses at discharge, and an evidence-based prescribing guideline resulted in decreased opioid usage in the first 30 days after surgery [36].…”
Section: Postoperative Interventionsmentioning
confidence: 99%
“…Other studies interested in postoperative opioid prescription volume have gathered data by liking pharmacy platforms and retrospectively gathering prescription data. 10,12,13 If these methods are not feasible, utilizing custom variable creation in ACS-NSQIP to gather prescription data is beneficial due to its prospective nature and ease of coordinating collection across a multi-institutional setting. As described, this method allows hospitals to review data collected during a sample period, which can lead hospitals to implement changes on custom variables to increase the quality of data collected for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Adding simple educational sessions that encourage the judicious prescription of opioids has been shown to decrease the amount of opioids prescribed by residents. 18,23 Coupling this education with system-wide changes, such as setting the default number of pills a provider orders through the electronic medical record to a lower number 20,24 or system-wide guideline development with educational programs aimed at all tiers of providers, 25,26 has also been shown to produce a durable reduction in the amount of OME prescribed while also not increasing the number of refills requested by patients.…”
Section: Discussionmentioning
confidence: 99%